Sutureless and Glue-free Conjunctival Autograft in Pterygium Surgery: A Case Series - Akanda, Md Ameenur Rashid; Ali, Yousuf; Ferdousi, Sharmin (TAJ: Journal of Teachers Association, 2020)
Foreign materials used in ocular surface surgery may lead to local complications such as discomfort, scarring, or infection. Plasma-derived products such as fibrin glue may produce possible hypersensitivity reactions whereas the risk of viral transmission remains. We describe a simple method of achieving conjunctival autograft adherence during pterygium surgery avoiding potential complications associated with the use of fibrin glue or sutures. Pterygium excision with limbal conjunctival autografting without using glue or sutures was performed in all the patients followed by bandaging for 24 hours. The patients were followed up post operatively on 2nd day, 1 week, 1 month, 3 month and 6 months. They were examined for haemorrhage, wound gape, graft shrinkage, chemosis, graft dehiscence, recurrence or any other complications. Total 100 cases were included in this case series. Patient age in ranged from 23 to 78 years (mean 50. 08 ± 12.76 years). Surgical Time was (in Minutes) from 20-28; mean & SD 23.76 ± 1.89. Total graft dehiscence occurred in 1 eye (1%), graft retraction in 12 eyes (12%) and recurrence was seen in 1 eye (1%). At 3 month postoperatively, the gain in uncorrected visual acuity ranged from 2-3 line in Snellen chart in 13 eyes. No other complication was noted. This simple technique for pterygium surgery may prevent potential adverse reactions encountered with the use of foreign materials and in this case series provided safe and comparable results to current methods. TAJ 2019; 32(2): 56-61